2010
DOI: 10.1016/j.fct.2009.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Threshold dose for peanut: Risk characterization based upon diagnostic oral challenge of a series of 286 peanut-allergic individuals

Abstract: Clinical records of 286 consecutive patients reacting positively with objective symptoms to double-blind, placebo-controlled oral peanut challenges at University Hospital, Nancy, France were examined for individual No Observed Adverse Effect Levels (NOAELs) and Lowest Observed Adverse Effect Levels (LOAELs). After fitting to a log-normal probability distribution model, the ED(10) and ED(05) were 14.4 and 7.3mg (expressed as whole peanut), respectively, with 95% lower confidence intervals of 10.7 and 5.2mg, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 15 publications
4
98
0
6
Order By: Relevance
“…diagnostic series, threshold-finding studies and immunotherapy trials) have reported on MED following challenge studies in adults and children combined (Oppenheimer et al, 1992;Leung et al, 2003;Lewis et al, 2005;Anagnostou et al, 2009), mostly in adults Hourihane et al, 1997;Nelson et al, 1997;Patriarca et al, 2006) (Wensing Marjolein et al, 2002), and mostly in children (Flinterman et al, 2006a;Clark et al, 2008;Clark et al, 2009;Blumchen et al, 2010;Nicolaou et al, 2010;Taylor et al, 2010;Wainstein et al, 2010;Blom et al, 2013). Studies are variable in size, challenge protocol used and type of food tested .…”
Section: Minimum (Observed) Eliciting Dosesmentioning
confidence: 99%
See 2 more Smart Citations
“…diagnostic series, threshold-finding studies and immunotherapy trials) have reported on MED following challenge studies in adults and children combined (Oppenheimer et al, 1992;Leung et al, 2003;Lewis et al, 2005;Anagnostou et al, 2009), mostly in adults Hourihane et al, 1997;Nelson et al, 1997;Patriarca et al, 2006) (Wensing Marjolein et al, 2002), and mostly in children (Flinterman et al, 2006a;Clark et al, 2008;Clark et al, 2009;Blumchen et al, 2010;Nicolaou et al, 2010;Taylor et al, 2010;Wainstein et al, 2010;Blom et al, 2013). Studies are variable in size, challenge protocol used and type of food tested .…”
Section: Minimum (Observed) Eliciting Dosesmentioning
confidence: 99%
“…EDp (expressed as milligrams of peanut and not as milligrams of protein, not included in Appendix A) were calculated by the same authors for peanut using two different datasets (Taylor et al, 2009b;Taylor et al, 2010). In the first study, data were obtained from 185 subjects participating in DBPCFCs for diagnostic purposes, because they were enrolled in immunotherapy trials, or for threshold-finding purposes.…”
Section: The Bench Mark Dose Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies to quantify the risk that undeclared peanut residue poses to peanut allergic consumers who may eat such products rely on population threshold distributions modeled from peanut allergic individuals who have undergone a low-dose peanut challenge using various market types of peanuts (Taylor et al, 2010. It is not known if different peanut market types have different potencies thereby affecting both individual and population-based thresholds for peanut.…”
Section: Introductionmentioning
confidence: 99%
“…The minimal eliciting dose (ED) refers to the lowest dose that can trigger an objective reaction in a controlled clinical challenge (Luccioli and Kwegyir-Afful 2014;Taylor et al 2010). The understanding of ED for individuals will improve consumers' quality of life and assist them in making more informed choices whilst purchasing food products (Luccioli and Kwegyir-Afful 2014).…”
Section: Quantitative Risk Assessment To Predict Allergenic Reactionsmentioning
confidence: 99%